Dual-wavelength passively Q-switched bulk laser using MoS2/graphene heterojunction. (May 2017) - Wang, Xihu; Xu, Jinlong; Gao, Shufang; Sun, Yijian; Zhu, Zhaojie; You, Zhenyu; Tu, Chaoyang
Graphical abstract: Highlights: MoS2 /G heterojunction based dual-wavelength passively Q-switched laser was realized. The MoS2 /G heterojunction was obtained by a facile hydrothermal reaction. A 355 ns pulse laser with pulse energy of 0.889 μJ was achieved. The pusle laser located at around 1047.2 and 1049.6 nm. Abstract: We demonstrate for the first time, to our certain knowledge, a dual-wavelength passively Q-switched bulk laser based on the MoS2 /graphene heterojunction saturable absorber. This heterojunction is prepared though a facile hydrothermal reaction and shows an excellent saturable absorption charateristic with the modulation depth of 9.12%. A 370 ns pulse laser with single pulse energy of 0.734 μJ is achieved. The corresponding output power and repetition frequency rate are 102 mW and 138.9 kHz, respectively. The stable pulse laser operates at 1047.2 and 1049.6 nm, simultaneously. This work validates the MoS2 /graphene heterojunction is a promising saturable absorber for multiwavelength near-infrared pulse lasers and it may broaden the range to choose optical modulator.